"When You Act Like an Adult, I’ll Treat You Like One . . .": Investigating Representations of Adulthood in Popular Culture - Shauna Pomerantz; Amanda Benjamin (Adult Education Research Conference, 2000)
Our paper critiques the traditional "What is an adult?" debate. Using television as text, we examine untraditional representations of adulthood in order to keep the term "adult" in constant play. We suggest the need to move away from fixed notions of maturity in lieu of a fluid understanding that is mediated by social and historical specificities.